Chapter L'immagine del Nome di Gesù presso i gesuati - Gallori, Corinna Tania (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
Given that the Jesuati were thus called because of their frequent invocation of "Jesus", it would stand to reason that they frequently displayed depictions of this name, the IHS, in their churches and settlements, as a testament to their devotion as well as a reference to their own nickname. And yet, their adoption of the Holy Name was not as straightforward as it first appears.